2017
DOI: 10.1111/petr.12914
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia after pediatric renal transplantation—The impact of immunosuppressive regimens

Abstract: Dyslipidemia contributes to cardiovascular morbidity and mortality in pediatric transplant recipients. Data on prevalence and risk factors in pediatric cohorts are, however, scarce. We therefore determined the prevalence of dyslipidemia in 386 pediatric renal transplant recipients enrolled in the CERTAIN registry. Data were obtained before and during the first year after RTx to analyze possible non-modifiable and modifiable risk factors. The prevalence of dyslipidemia was 95% before engraftment and 88% at 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…After transplantation, the risk of dyslipidemia is compounded by the effects of commonly used immunosuppressive agents, including corticosteroids, CNIs and mechanistic target of rapamycin (mTOR) inhibitors. A recent registry study of 386 pediatric transplant recipients reported hypertriglyceridemia in 71% of children at 3 months posttransplant and 59% at 1 year posttransplant and hypertriglyceridemia was associated with lower glomerular filtration rate (GFR) [ 37 ]. Corticosteroids alter lipoprotein metabolism and promote dyslipidemia by stimulating hepatic synthesis of very-low-density lipoprotein (VLDL) and down-regulating LDL receptors [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…After transplantation, the risk of dyslipidemia is compounded by the effects of commonly used immunosuppressive agents, including corticosteroids, CNIs and mechanistic target of rapamycin (mTOR) inhibitors. A recent registry study of 386 pediatric transplant recipients reported hypertriglyceridemia in 71% of children at 3 months posttransplant and 59% at 1 year posttransplant and hypertriglyceridemia was associated with lower glomerular filtration rate (GFR) [ 37 ]. Corticosteroids alter lipoprotein metabolism and promote dyslipidemia by stimulating hepatic synthesis of very-low-density lipoprotein (VLDL) and down-regulating LDL receptors [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Habbig et al . carried out a retrospective cohort study on data reported to the CERTAIN registry (http://www.certain-registry.eu).…”
Section: The Study By Habbig Et Almentioning
confidence: 99%
“…While published literature has described the elevated cholesterol and triglyceride levels often seen in adult renal transplant patients, there are little data describing these same levels in pediatric renal transplant recipients. With that in mind, we were delighted to see a careful evaluation of dyslipidemia in 386 pediatric renal transplant recipients from the Cooperative European Paediatric Renal Transplant Initiative (CERTAIN) in this issue of Pediatric Transplantation …”
Section: Introductionmentioning
confidence: 99%
“…It is likely that calcineurin inhibitors (CNIs) will continue to be prescribed in the near future, and their association with synergistic drugs may allow using them at lower target levels . Due to their side effects, especially mouth ulcers and dyslipidemia, mTOR inhibitors, although non‐nephrotoxic, remain challenging . Newer immunosuppressive protocols with stronger antirejection drugs often have unfavorable infections or cancer complications.…”
Section: Introductionmentioning
confidence: 99%
“…3 Due to their side effects, especially mouth ulcers and dyslipidemia, mTOR inhibitors, although non-nephrotoxic, remain challenging. [4][5][6] Newer immunosuppressive protocols with stronger antirejection drugs often have unfavorable infections or cancer complications. The challenge that lies ahead is to extend allograft survival time while simultaneously reducing the side effects of immunosuppression.…”
Section: Introductionmentioning
confidence: 99%